PRACTICING ENGLISH SPEAKING ONLINE INTERNATIONALLY: THE PERCEPTIONS OF INDONESIAN HALLO USERS - Naofal Nasir, Rahmat; Ariyani, Amra; Anwar Korompot, Chairil (JTechLP: Journal of Technology in Language Pedagogy, 2022)
This study aims to ascertain how users think about Hallo (https://www.hallo.ai), a free artificial intelligence (AI) application (app) that enables users to interact with AI teachers to learn languages. Hallo has become increasingly popular among EFL students worldwide as a platform for practicing English. In conducting this study, the researchers used a qualitative descriptive method and collected the data using in-depth interviews with twenty Hallo users from Indonesia who were chosen using a purposive sampling technique. Findings from the data analysis showed that Hallo contributes to the users' increased ability and confidence in speaking English. With Hallo, users can communicate anonymously, get a lot of exposure to others, connect with people who share their goals and are on the same level as them, and come across supportive individuals. Users see English-speaking ability as influenced by two of the indicators of speaking skills: accuracy and fluency. This is because users engage in worldwide online EFL speaking practice with strangers or foreigners and are sensitive to cultural variations. Users impart accurate knowledge, pay less attention to grammar, develop pronunciation, and increase their vocabulary. Users are exposed to interlocutors frequently, their proficiency has an impact on users, users are under the influence of external forces, and users experience issues with their internet connections. In conclusion, users generally had positive perceptions of Hallo's contributions to their improved English-speaking proficiency and confidence. As a result, Hallo could be a fantastic tool for EFL learners to practice speaking.